Modeling Creativity and Enjoyment in Learning Statistics Online in the New Normal - Casinillo, Leomarich F. (Philippine Social Science Journal, 2022)
In any school, creative learning as an enjoyable experience for students signals effective cognitive thinking in the teaching-learning environment. This study targets to explain the level of how creative and enjoyable learning statistics and determine its cognitive factors among students amid the COVID-19 pandemic. The study exploited secondary data from an existing study and analyzed it using descriptive statistics and regression modeling. Results showed that learning statistics during the pandemic is “moderately" creative (M=6.07, SD=1.86) and "moderately" enjoyable (M=5.78, SD=1.98). Based on Pearson correlation and simple regression, if the level of creativity increases, it is more enjoyable to learn statistics online. The regression model reveals that internet signal, students using cell phones, and how rewarding learning statistics is as significant predictors of creativity. Additionally, for older students, how rewarding learning statistics, physical health, and lower statistics anxiety are the significant determinants of enjoyment level in learning statistics online. In that case, to maintain creativity and enjoyment in learning statistics amid the pandemic, it is suggested that teachers must encourage and show a positive attitude to the students to lower their anxiety levels. Furthermore, teachers must consider interesting and healthy learning activities to step up the creative ideas of students and enjoy learning despite the adverse effect of the pandemic.